Hubungan Pengetahuan dengan Peran Kader Posyandu Balita dalam Capaian Imunisasi Dasar Lengkap di Wilayah Kerja Puskesmas Bahaur Hilir Kabupaten Pulang Pisau - Angga Renaldi; Karmitasari Yanra Katimenta; Henry Wiyono (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Knowledge and the role of posyandu (integrated service post) cadres are crucial and strategically important in providing health education to the community. According to 2023 data, the coverage of complete basic immunization at posyandu is significantly below the target. Surveys revealed that some cadres have insufficient knowledge and a minimal role in immunization services, such as providing counseling, encouraging, and motivating mothers to immunize their children. This study aims to determine the relationship between knowledge and the role of posyandu cadres in achieving complete basic immunization in the working area of Puskesmas Bahaur Hilir, Pulang Pisau District. Method: This research is a correlational study with a quantitative method using a cross-sectional approach. The sampling technique employed was total sampling, with 65 respondents. Data were collected using a questionnaire, and statistical analysis was performed using the Spearman correlation test. Results: The data analysis revealed a significant relationship between knowledge and the role of cadres, with a significance value (p-value) of 0.000 < 0.05 and a strong correlation coefficient of 0.642. Conclusion: There is a significant relationship between knowledge and the role of cadres, with a strong correlation coefficient. It is recommended that posyandu cadres enhance their knowledge and active participation in posyandu activities and communicate information to the community to improve health outcomes.